Peran Media Sosial dalam Kesantunan Berbahasa Siswa di Lingkungan SMA Negeri 1 Seririt - I Gusti Ayu Putu Pradnyani; I Wayan Rasna; Ida Bagus Putrayasa (LP. Ma'arif Janggan Magetan, 2024)
This study aims to explain the role of WhatsApp social media in students' language politeness, violations of the principle of student language politeness and students' use of language in association in the environment of SMA Negeri 1 Seririt. The design of this study is qualitative descriptive. This research uses observation, interview, documentation and record methods. The data analysis techniques of this research are, data collection, data reduction, data presentation, and conclusion drawn. The results of the study showed that there was a tendency to use emoticons/emojis intensively, shortcomings in the use of punctuation and the use of informal language with abbreviations or slang on WhatsApp social media. There are 20 types of data classified as violations of the principle of politeness in Leech which include violations of the maxim of wisdom, maxim of generosity, maxim of appreciation, maxim of simplicity, maxim of compatibility and maxim of sympathy. There are forms of students' use of language in school from the choice of words, sentence structure, and different levels of formality.